1996
DOI: 10.1364/ao.35.006976
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel single-output color pattern recognition by use of a joint-transform correlator

Abstract: A novel method for performing color image recognition by the use of the coherent joint-transform correlator is introduced. The input plane of the proposed method is a spatial rearrangement of the separation into color channels of both the color input scene and the color target. This input plane is gray scaled and monochromatic, thus it can be displayed by the use of amplitude spatial light modulators to achieve real-time operation. The system provides a single output-plane result of the optical coherent additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…However, the multi-channel single output color JTC has to take into account the separation between the input target image and the reference image. Deutsch [21] found that the separation between the input target image and the reference image for the same color must be the same and also larger than the sum of the widths of these images in order to prevent any unwanted overlapping between correlation outputs. To yield sharp correlation peaks, Alam et al proposed a fringe-adjusted JTC based on Newton-Raphson algorithm [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the multi-channel single output color JTC has to take into account the separation between the input target image and the reference image. Deutsch [21] found that the separation between the input target image and the reference image for the same color must be the same and also larger than the sum of the widths of these images in order to prevent any unwanted overlapping between correlation outputs. To yield sharp correlation peaks, Alam et al proposed a fringe-adjusted JTC based on Newton-Raphson algorithm [22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a spatial light modulator (SLM) is needed at each channel, two lenses are required at each channel, and an extra beam splitter and a mirror are also needed. The concept of multi-channel single output color JTC configuration was initially proposed by Deutsch to overcome such disadvantages [21]. However, the multi-channel single output color JTC has to take into account the separation between the input target image and the reference image.…”
Section: Introductionmentioning
confidence: 99%
“…However, the multi-channel single output color JTC has to take into account the separation between the input target image and the reference image. Deutsch [21] found that the separation between the input target image and the reference image for the same color must be the same and also larger than the sum of the widths of these images in order to prevent any unwanted overlapping between correlation outputs. To yield sharp correlation peaks, Alam et al proposed a fringe-adjusted JTC based on the Newton-Raphson algorithm [22].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it could be possible to find an arrangement of objects for all color channels at the input plane that would lead to the coherent addition of the three cross-correlation terms between the corresponding RGB color channels of the target and the input scene. To achieve this, Deutsch et al [8] introduced a multichannel single-output JTC. However, their concept led to massive zero-order parts composed of several autocorrelation terms that suffer from poor detection efficiency.…”
Section: Introductionmentioning
confidence: 99%